Scanning Electron Microscopy of Bacterial Colonies - Afrikian, Evrik G. (1973)
A technique is described for observing bacterial colony growth. Bacillus cereus, B. subtilis, and B. cereus var. mycoides were grown on strips of dialysis membrane layered on nutrient agar. Microcolonies of the organisms on strips were fixed in Formalin vapor in situ; the strips then were removed from the agar and secured to scanning microscope specimen stubs without markedly disturbing the cellular arrangement. Scanning electron micrographs clearly depict morphology of individual cells, as well as the spatial orientation of cells within the colony. This technique is reproducible, adaptable, and simple.